2019
DOI: 10.1186/s42826-019-0010-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of the response with botulinum toxin muscle injection in the ICR mice from three different sources

Abstract: Botulinum-toxin A (BoNT/A) is a widely used not only for cosmetics but also for various experimental purposes including muscle-related research. In this study, we applied BoNT/A to mouse muscle of three different sources to compare and evaluate the biological and pathological response. The three different mouse sources consist of Korl: ICR (Korea FDA source), A:ICR (USA source) and B:ICR (Japan source) which were purchased from each different vendors. To compare the responses of ICR mice with BoNT/A muscle inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…This study also evaluated the hematological effects of BOTOX injections, and we found a significant decline in Hb level in the group receiving "only BOTOX." In agreement with our findings, a recent investigation into the effect of BoNT/A injections on mice showed a significant decrease in RBC count, Hb level, and hematocrit (24). However, the reasons for this reduction in Hb level are not well understood, as it is well known that some medications may cause a decrease in Hb level (32), so the effect of BOTOX and HA injection needs further investigation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study also evaluated the hematological effects of BOTOX injections, and we found a significant decline in Hb level in the group receiving "only BOTOX." In agreement with our findings, a recent investigation into the effect of BoNT/A injections on mice showed a significant decrease in RBC count, Hb level, and hematocrit (24). However, the reasons for this reduction in Hb level are not well understood, as it is well known that some medications may cause a decrease in Hb level (32), so the effect of BOTOX and HA injection needs further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Another study involving adult albino rats showed that BOTOX injections in the bones and bone marrow increased ALP. [24], while the present study showed a significant decrease in ALP in the group injected with BOTOX and HA filler. In line with our findings, an analysis performed in 2019 illustrated a reduction in the ALP level of mice injected with botulinum toxin (24).…”
Section: Discussioncontrasting
confidence: 43%
“…The biochemical analysis was validated using a Cobas 8000 C702 chemistry analyzer (Roche, Mannheim, Germany). Components including ALT, AST, BUN, creatinine, and calcium were detected as previously described [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Until now, the biological phenotypes of Korl (Korl:ICR, C57BL/6NKorl, BALB/cKorl and DBA/2Korl) were compared with other substrains provided by commercial venders, to verify the stability of their characteristics. These phenotypes showed similar responses to various disease-inducing agents in cancer biology, neurobiology, immunology and microbiology [ 13 16 ]. As part of the current study, we investigated the influence of BALB/cKorl substrain background on DMBA+TPA induced skin carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%